Pengaruh Penggunaan Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Kelas IX MTs Darunnajah 2 Cipining Bogor - Isna Zaqiatul Munna; Musthafa Zahir; Yogi Saputra (Journal of International Multidisciplinary Research, 2024)
Based on the background of the problem that has been explained by the researcher, it has been clarified into several problems as follows: 1. There are still many female students who ignore or underestimate the lessons of moral aqidah 2. The ongoing learning process is less interesting so that students feel bored quickly. 3. Only some students understand the explanation given by the teacher. 4. Lack of student activity (question and answer) when learning takes place. 5. There are still many students who are reluctant to pay attention to the teacher explaining the material. The research method used by the author is quantitative research. The population in this study was all 30 students in class IX M at MTs Darunnajah 2 Cipining. This shows that student learning outcomes in the subject of moral aqidah have a very high level. Based on the research results, there is a significant positive influence of the use of learning media on student learning outcomes in the moral aqidah subject at MTs Darunnajah 2 Cipining Bogor. This is proven by the calculation results of the equation Y 140.383 + 0.219 In the table for testing the significance of the regression line equation from the 5th column regression row, namely Fcount (b/a) 1.407, and p-value 0.245 > 0.05, so that H0 is accepted, it can be concluded that the regressions of Y and X are significant. The correlation coefficient value obtained r_xy 0.219 < r_table 0.374 is included in the weak correlation because it is in the value range 0.20-0.39. The results of the coefficient of determination show that visual learning media (print) has an influence of 4.8% on student learning outcomes, while 95.2% is influenced by other factors.